2015
DOI: 10.1152/ajpheart.00627.2015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between biventricular myocardial performance and metabolic parameters during incremental exercise and recovery in healthy adolescents

Abstract: Pieles GE, Gowing L, Forsey J, Ramanujam P, Miller F, Stuart AG, Williams CA. The relationship between biventricular myocardial performance and metabolic parameters during incremental exercise and recovery in healthy adolescents. Am J Physiol Heart Circ Physiol 309: H2067-H2076, 2015. First published October 23, 2015 doi:10.1152/ajpheart.00627.2015 and right ventricular (RV) myocardial reserve during exercise in adolescents has not been directly characterized. The aim of this study was to quantify myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 52 publications
5
27
1
Order By: Relevance
“…There is a paucity of research with respect to the quantification of regional wall deformation during exercise in pre‐adolescent populations. Recent work by Pieles et al demonstrated a pattern of increased peak longitudinal ε from rest with a subsequent plateau during submaximal, supine cycle ergometry in recreationally active boys and girls (13.2 years). Furthermore, adult data during supine and semi‐supine exercise also demonstrates a similar a pattern for peak longitudinal ε .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of research with respect to the quantification of regional wall deformation during exercise in pre‐adolescent populations. Recent work by Pieles et al demonstrated a pattern of increased peak longitudinal ε from rest with a subsequent plateau during submaximal, supine cycle ergometry in recreationally active boys and girls (13.2 years). Furthermore, adult data during supine and semi‐supine exercise also demonstrates a similar a pattern for peak longitudinal ε .…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of speckle tracking echocardiography (STE), which reliably assesses regional myocardial tissue deformation in the longitudinal plane of motion has the potential to provide further mechanistic insight into the link between LV performance and maximal aerobic capacity. There are a small number of studies that have characterized cardiac deformation during exercise in the child and adolescent populations . To date, this approach has not been adopted in highly trained pre‐adolescent soccer players in an attempt to differentiate the impact of training status on regional LV function.…”
Section: Introductionmentioning
confidence: 99%
“…For example, among a cohort of 23 healthy adolescents undergoing cardiopulmonary exercise testing, Pieles et al reported that both RV and LV strain increased in relation to work rate (p<0.05). 32 Moreover, among 44 chronic obstructive pulmonary disease patients, Caminiti et al reported that those with RV dysfunction (as defined via TAPSE) had lower effort tolerance on baseline 6 minute walk test (p=0.02) and lesser improvement following cardiopulmonary rehabilitation (p<0.001). 33 Other studies conducted among patients with LV systolic dysfunction have linked reduced RVEF to impaired exercise capacity as measured via peak oxygen consumption (V0 2 max) during bicycle ergometry or treadmill exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Still, Doucende et al did not observe a statistically significant increase between final work intensities, making it difficult to determine whether at 40% maximal workload, GCS begins to plateau thereafter or larger workload increments are necessary to elicit notable differences between exercise intensities. Further, circumferential shortening during exercise also shows regional disparity between apical and basal planes, with increases at the apex (ACS) without changes at the base (BCS), which, however, contrasts another investigation having reported a reserve in BCS compared with baseline …”
Section: Introductionmentioning
confidence: 92%
“…Further, circumferential shortening during exercise also shows regional disparity between apical and basal planes, with increases at the apex (ACS) without changes at the base (BCS), 9,10 which, however, contrasts another investigation having reported a reserve in BCS compared with baseline. 11 Data pertaining to circumferential strain during resistance exercise are limited. Reductions in GCS were noted during isometric hand-grip exercises 7,12 ; however, regional strains were not independently reported.…”
Section: Introductionmentioning
confidence: 99%